THE CO-TEXT AS CONTEXT: KRLEŽA’S IZLET U RUSIJU [AN EXCURSION TO RUSSIA] AND VINAVER’S RUSKE POVORKE [RUSSIAN PROCESSIONS] - BrebanovićPredrag (Philological Studies, 2019)
The paper examines the intertextual connections between Stanislav Vinaver and Miroslav Krleža. Comparison of the diffirent versions of their travelogues reveals that Krleža’s An Excursion to Russia (1926) contains many traces of Vinaver’s Russian Processions (1924). These specific traces are explained by the history of the mutual relations between the two writers, with particular reference to the polemics they led during 1920s and 1930s. Textual analysis reveals two different types of travelogue and two different poetics: one of modernism (Vinaver’s), and the other of avant-garde (Krleža’s).